Media crossing borders : fourth regional workshop, Kathmandu, Aug. 30-Sept. 1, 2003 - South Asia Forum for Human Rights. Regional Workshop 2003 : Kathmandu, Nepal); Manchanda, Rita.; South Asia Forum for Human Rights (Kathmandu : South Asia Forum for Human Rights, 2004)
Contributed articles with reference to South Asia presented at fourth Regional Workshop of South Asia Forum for Human Rights held at Kathmandu, Nepal in 2003.
Keywords: Mass media -- South Asia -- Congresses; Social conflict in mass media -- Congresses; Boundaries -- Congresses